Pemidanaan Korporasi Dalam Perkara Tindak Pidana Korupsi Dan Konsep Pertanggungjawabannya - Mario Setyo Nugroho (Sebelas Maret University, 2017)
This study aims to perceive coroporate criminal prosecution in a corruption case in the telecommunication sector and to discover the concept of corporate responsibility in Supreme Court verdict Number: 787 K/Pid.Sus/2014. At fisrt PT. IM2 as providers of services in carrying out its activities can only use the closed remain network. By simply using a closed remain network, PT. IM2 as providers of services network is not optimal in providing services to customers for a limited scope of services. Then to avoid ability to pay Up Front Fee and the Cost of Usage Right radio frequency band to the state, defendant as if cooperation network usage for broadband internet access but in fact unlawfully using the frequencies 2.1 GHz owned by PT. Indosat Tbk. The impact of the actions of the defendant has enriched PT. IM2 and PT. Indosat 1.483.991.195.970,00 and financially harm the country as much as Rp 1.358.343.346.674,00(One billion three hundred and fifty-eight billion three hundred and forty three million three hundred and forty six thousand six hundred and seventy-four rupiah). Based on the results of this study it can be concluded that the system of corporate criminal liability has reached the stage where corporations can commit a crime and be accountable. In sentencing a corporation known double track system which adopted two lanes of punishment, in the sense that in addition to the criminal may also be a variety of actions to the corporation as a maker or criminal. Keywords: corporate criminal prosecution, corruption